1995
DOI: 10.1111/j.1469-7610.1995.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Savants, Segments, Art and Autism

Abstract: This study describes two experiments which investigate pattern construction by graphically gifted, autistic savants. We explore whether the notion of weak central coherence in autism might be extended to account for the relatively high frequency of savants among the autistic population. We also suggest that an awareness of constituent segments in wholes may be relevant to artistic talent in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 8 publications
10
75
2
1
Order By: Relevance
“…Mottron & Belleville (1993) provided the example of a savant artist who approached his drawings in a piecemeal fashion, while a professional draughtsman who served as a control used outlines in his drawings initially, then progressed to more detailed elements. Furthermore, both savant artists with autism and typically developing artists obtain high scores on the block design task (Pring et al 1995). This shared facility for segmenting patterns in both artists and those with autism suggests that WCC may contribute to the over-representation of savant skills in ASD.…”
Section: Introductionmentioning
confidence: 98%
“…Mottron & Belleville (1993) provided the example of a savant artist who approached his drawings in a piecemeal fashion, while a professional draughtsman who served as a control used outlines in his drawings initially, then progressed to more detailed elements. Furthermore, both savant artists with autism and typically developing artists obtain high scores on the block design task (Pring et al 1995). This shared facility for segmenting patterns in both artists and those with autism suggests that WCC may contribute to the over-representation of savant skills in ASD.…”
Section: Introductionmentioning
confidence: 98%
“…A trick used in teaching accurate drawing to TD students is to copy pictures turned upside down: inversion disproportionately disrupts configural processing. Pring et al (1995) reported that block design skill, which may result from ability to see the parts within the to-be-copied design, was notable in children with artistic abilities and in children with autism. In the area of calendar calculation, too, Heavey has suggested that the starting point may be the discovery of small day-date regularities (Heavey et al 1999).…”
Section: (B) Executive Dysfunctionmentioning
confidence: 99%
“…Segmentation strategy is thought to be a precursor to savant skill (Pring and Hermelin, 2002). So, although autism is a disorder characterised by impairment, WCC and segmentation strategy highlight the superiority in specific areas of individuals with autism over those without autism (Pring, Hermelin and Heavey, 1995;Happe, 1999) -a concept that fits in well with savant syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Stephen Wiltshire in Sacks, 1995) and calendrical calculators (Pring & Hermelin, 7 2002). Thus AP may be not only vital to musical savants, but an important attribute of savant syndrome itself (Pring, Hermelin & Heavey, 1995). Additionally, the fact that AP develops without explicit learning (Zatorre, 2003) underlines the implicit nature of the acquisition of savant knowledge networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation